Perancangan Karya Busana Evening dari Bahan Batik Nitik dengan Sumber Ide Bunga Kemuning - Ms Jumariah; Sri Purwani; Maya Rustiandari (Jurnal Socia Akademika, 2020)
Evening dress is clothing made from a nice material and an interesting decoration that looks beautiful and the dress in the age of the long dress is worn at the party night. Evening dress accentuates the majesty of Fashion aesthetics, both in terms of model and colour harmony. This is what motivates the writer to make creativity making "Evening fashion planning from Batik Nitik material with the idea of flowers Kemuning". Nitic Batik which has a simple motif and antiquity only serve as a jarik worn by parents, and now only limited to the cultivation of shirts and skirts. Writers are challenged to raise the selling value and the value of batik Nitik, as evening dress by taking the source of the idea of the beauty of the yellow flower that has a fragrant scent that soers the good and beautiful fragrance. In the design of evening clothing from batik Nitik material in addition to using the source of the idea of kemuning writers also give decorations on the gold-led nitic batik, embroidery applications, sequin, corsage of batik nitic material so that the evening fashion design looks beautiful, luxurious and exclusive.